Effect of three bio-stimulants in the morphologic and productive behavior of radish crops (Raphanus sativus L.) - Hurtado, Alexander Calero [UNESP] (2019)
With the objective to evaluate the effect of three bio-stimulants in the productive behavior of crops radish, was developed the experiment in the garden areas of “El Estadio” belonging to urban agriculture of Sancti Spíritus during the months of February to April of 2016. The treatments were: ME-50, 50 mL.L-1, lixiviate vermicomposting humus, 100 mL.L-1and Biobras-16, to dosage of 0.012 L.ha-1 and the water control. The morphagronomic parameters observations were on 45 plants per treatment and the observed variables were the average of leaf per plant, high average per plants (cm), average of diameter of roots (cm), biomass production (g.plant-1), yields (kg.m-2) and percentage of tuber roots afected (cracks roots) (%). The results showed that the use of three bio-stimulants in radish crops production in garden conditions, since it had positive effect because increasing the media production of leaf per plant, average of diameter of roots, biomass production, the yields than 1.05 kg.m-2, in addition, the treatment with ME-50 reduced the percentage of damaged tuberous root by 50% less in relation to the control.